Association Between Socioeconomic Status and Obesity in Adults: Evidence From the 2001 to 2009 Korea National Health and Nutrition Examination Survey - Jihye Kim; Shreela V. Sharma; Sung Kyun Park (Korean Society for Preventive Medicine, 2014)
ObjectivesThe present study examined relationships between socioeconomic status (SES) and obesity and body mass index (BMI) as well as the effects of health-related behavioral and psychological factors on the relationships.MethodsA cross-sectional population-based study was conducted on Korean adults aged 20 to 79 years using data from the 2001, 2005, and 2007 to 2009 Korea National Health and Nutrition Examination Survey. Multivariate logistic and linear regression models were used to estimate odds ratios of obesity and mean differences in BMI, respectively, across SES levels after controlling for health-related behavioral and psychological factors.ResultsWe observed significant gender-specific relationships of SES with obesity and BMI after adjusting for all covariates. In men, income, but not education, showed a slightly positive association with BMI (p<0.05 in 2001 and 2005). In women, education, but not income, was inversely associated with both obesity and BMI (p<0.0001 in all datasets). These relationships were attenuated with adjusting for health-related behavioral factors, not for psychological factors.ConclusionsResults confirmed gender-specific disparities in the associations of SES with obesity and BMI among adult Korean population. Focusing on intervention for health-related behaviors may be effective to reduce social inequalities in obesity.